(untitled) (Journal of Rangpur Medical College, 2025)
Background: Tuberculosis (TB) remains a major public health concern in Bangladesh, with significant variability in its demographic, clinical, and management aspects. Objective: This study aims to assess the age and genderspecific burden of TB in a rural Bangladeshi population, emphasizing diagnostic approaches, symptom variation, and management strategies. Methods: This retrospective study was conducted from October 1, 2023, to September 30, 2024, at the Directly Observed Treatment, Short Course (DOTS) Centre of Kumudini Hospital, Mirzapur, Tangail, Bangladesh. A total of 429 participants (356 adults, 73 children) were diagnosed and managed under DOTS, with data collected via clinical evaluations, X-rays, MT, GeneXpert, FNAC, and ADA tests, and analyzed using SPSS 26. Results: Pulmonary TB (PTB) accounted for 53.85% of cases, with 37.30% bacteriologically confirmed and 16.55% clinically diagnosed. Extrapulmonary TB (EPTB) constituted 46.15% of cases, with cervical lymph node TB being the most prevalent subtype (83.33% of EPTB cases). Age distribution showed a higher burden of PTB in individuals aged >65 years (22.50% bacteriologically confirmed and 32.39% clinically diagnosed), whereas EPTB was most frequent among participants aged 25–<35 years (19.70%) and 35–<45 years (18.18%). Gender analysis revealed a male predominance in bacteriologically confirmed PTB (71.88%) and clinically diagnosed PTB (60.56%), while EPTB was more frequent in females (59.09%). Conclusion: The study reveals age and genderspecific disparities in TB, with older adults mainly affected by PTB and younger adults and females more prone to EPTB, highlighting the need for targeted strategies and improved healthcare access in high-burden areas. J Rang Med Col. March 2025; Vol.10, No.1: 87-92